Tillskottsutfodring av smågrisar under digivningsperioden - Ivarsson, Emma (2007)
Weaning is one of the most critical events in the piglet production with problems such as growth check and post-weaning diarrhea as a result. The lighter the piglets are when the growth check occurs, the harder they have to get back to normal growth rate. Creep feeding of piglets is used to reduce the problems by increasing the weaning weight and adapting the digestive tract to a starter diet. Hodge (1974) showed that the sow's milk can not provide enough nutrients for maximal growth rate. Artificially reared piglets showed a growth rate twice that of the sow-reared piglets. The potential to increase the growth rate during the suckling period is high and so is also the interest for creep feeding. The aim of this thesis was to study the effect on production results when piglets are fed the milk based creep feed Parvel, which is fed dry during the suckling period. The report also includes a review of known effects of creep feeding.